Deficiency of S100 calcium binding protein A9 attenuates vascular dysfunction in aged mice - Zhao, Boying; Yu, Jiang; Luo, Yuan; Xie, Ming; Qu, Can; Shi, Qiong; Wang, Xiaowen; Zhao, Xingji; Kong, Lingwen; Zhao, Yu; Guo, Yongzheng (Redox biology, 2023)
S100 calcium-binding protein A9 (S100A9) is a danger-associated molecular pattern molecule that mediates the inflammatory response. Inflammation is essential in aging-related cardiovascular diseases. However, less is known regarding the role of S100A9 in vascular aging. S100A9 null mice were used to investigate the role of S100A9 in aging-related pathologies. Artery rings were used to measure the functional characteristics of vascular with a pressurized myograph. Telomere length, Sirtuin activity, oxidative stress, and endothelial nitric oxide synthetase (eNOS) activity were used to elevate vascular senescence. Intraperitoneal glucose tolerance (IPGTT) and insulin sensitivity test (IST) were employed to investigate the effects of S100A9 on insulin resistance. Inflammation response was reflected by the concentration of inflammatory cytokines. The Toll-like receptor 4 (TLR4) and receptor for advanced glycation end products (RAGE) inhibitors were used to identify the downstream molecular mechanisms of S100A9 in aging-induced senescence in endothelial cells. S100A9 expression in vascular increased with aging in mice and humans. Deficiency of S100A9 alleviated vascular senescence in aged mice, as evidenced by increased telomere length, Sirtuin activity, and eNOS activity. Meanwhile, S100A9 knockout improved endothelium-dependent vasodilatation and endothelial continuity in aged mice. Moreover, the increased insulin resistance, oxidative stress, and inflammation were mitigated by S100A9 deletion in aged mice. In vitro, S100A9 induced senescence in endothelial cells, and that effect was blunted by TLR4 but not RAGE inhibitors. The present study suggested that S100A9 may contribute to aging-related pathologies and endothelial dysfunction via the TLR4 pathway. Therefore, targeting S100A9/TLR4 signaling pathway may represent a crucial therapeutic strategy to prevent age-related cardiovascular diseases. •S100A9 contributed to aging-related pathologies, such as insulin resistance, oxidative stress and inflammation.•Deficiency of S100A9 alleviated endothelial dysfunction and improved vascular function in aged mice.•TLR4 pathway was involved in the regulation of S100A9-induced cellular senescence in human aortic endothelial cells.